Increasing mumps incidence rates among children and adolescents in the Republic of Korea: age–period–cohort analysis - Young-June Choe; Young Hwa Lee; Sung-Il Cho (International Journal of Infectious Diseases, 2017)
Background: To characterize the temporal dynamics of mumps epidemiology according to the different vaccine strains used, sex-specific trends were decomposed in an age–period–cohort (APC) analysis for mumps cases reported in South Korea. Methods: National surveillance data were used to describe the epidemiology of mumps cases from 2001 to 2015. An APC model was used to break down the reported mumps cases into the effects of age, period, and birth cohort. Results: From 2001 to 2015, the incidence started to increase from fewer than 10 cases to more than 100 cases per 100 000. The incidence rate was highest among males aged 15–17 years during 2013–2015, reaching 508.7 per 100 000 persons. There was an increased incidence during the late teenage years in the 1998–2000 cohort. An age shift towards the earlier teenage years was observed across the 2001–2003 and 2004–2006 cohorts. The risk of mumps increased according to the birth cohort; the net drift from 2001 to 2015 was 27.67 (95% confidence interval 27.5.47–29.90) for males and 27.25 (95% confidence interval 24.91–29.65) for females. Conclusions: The increase in mumps seen in Korea may have been affected by the birth cohort exposed to the Rubini strain; however other factors may have contributed to the increase in non-exposed cohorts.